2005
DOI: 10.1007/s10809-005-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-property relationships in the series of diazonium cations, intermediate products in the synthesis of analytical forms and dyes

Abstract: The azocoupling reaction of aromatic amines and phenols with aryldiazonium cations is of great importance for the production of dyes [1][2][3] and in analytical chemistry [4].Diazonium cations can be reduced either chemically or electrochemically [5][6][7][8][9][10][11][12]. For many compounds, the abilities to be subjected to electrophilic (nucleophilic) attack and to undergo oxidation (reduction) vary in parallel [13][14][15][16]. The susceptibility of diazo cations to reduction can serve as a measure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Nonetheless, the addition of radical inhibitors and trapping reagents, including 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), 2,6-di- tert -butyl- p -hydroxytoluene (BHT), and 1,1-diphenyl ethylene (DPE), to the reaction systems of methods 1 and 2 did not significantly affect the reaction efficiencies (please see the Supporting Information, section 6.1). The kinetic experiments of diazotization using infrared spectroscopy showed that two distinct absorption peaks (2340 and 2360 cm –1 ) appear in the range of 2300–2400 cm –1 , which refer to the NN bond vibration, and their intensity increased as the reaction progressed (please see the Supporting Information, Figure S8c). An absorption band at 1457 cm –1 also occurs, which may correspond to the NN bond stretching mode (please see the Supporting Information, Figure S8d).…”
mentioning
confidence: 99%
“…Nonetheless, the addition of radical inhibitors and trapping reagents, including 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), 2,6-di- tert -butyl- p -hydroxytoluene (BHT), and 1,1-diphenyl ethylene (DPE), to the reaction systems of methods 1 and 2 did not significantly affect the reaction efficiencies (please see the Supporting Information, section 6.1). The kinetic experiments of diazotization using infrared spectroscopy showed that two distinct absorption peaks (2340 and 2360 cm –1 ) appear in the range of 2300–2400 cm –1 , which refer to the NN bond vibration, and their intensity increased as the reaction progressed (please see the Supporting Information, Figure S8c). An absorption band at 1457 cm –1 also occurs, which may correspond to the NN bond stretching mode (please see the Supporting Information, Figure S8d).…”
mentioning
confidence: 99%